Stabilization mechanism of ZnO quantum dots - Peukert, Wolfgang; Marczak, Renata; Schäfer, Stefan; Segets, Doris (Nanotechnology 2010: Advanced Materials, CNTs, Particles, Films and Composites - 2010 NSTI Nanotechnology Conference and Expo, NSTI-Nanotech 2010, 2010)
The current work addresses the understanding of the stabilization of small ZnO quantum dots in ethanolic suspension. Thereby different degrees of purification were investigated. The results revealed that not only the well-known ζ-potential as a representative for the surface charge determines the colloidal stability but also the surface coverage of acetate groups bound to the particle surface. Those acetate groups act as molecular spacers between the nanoparticles and prevent agglomeration. Regarding DLVO-calculations using a core-shell model, not only the height of the maximum but also the depth of the primary minimum has to be considered to see if a colloidal suspension is stable or not.
Keywords: Core-shell model; Purification; Quantum dot; Stability; ZnO